Patient and employee safety in pre-hospital healthcare: Key findings from 2019–2024 research - Ugur Ugrak; Safak Cinar (Medicine Science)
This systematic review aims to synthesize and present the findings of studies conducted between 2019 and 2024 on patient and employee safety in pre-hospital healthcare. A total of 268 studies were identified through a database search structured according to the study's purpose across databases of ScienceDirect (n=131), Web of Science (n=50), and PubMed (n=105). Following a systematic screening aligned with the study criteria, 26 studies were selected for synthesis. The systematic review followed a typology combining systematic search and review methods and adhered to the "PRISMA" checklist to guide the research process. This systematic review indicates that the safety culture in pre-hospital healthcare was inadequate and that lack of training negatively affected patient and employee safety. The negative effects of factors such as the COVID-19 pandemic, lack of equipment, and increased stress on the pre-hospital healthcare culture were emphasized. The importance of standard procedures for preventing accidents in patient transfer processes was stressed. This systematic review reveals that the safety culture in pre-hospital healthcare should be strengthened, training programs should be made comprehensive, and standard operational procedures should be developed. In addition, this study also shows the need to develop safety measures for patient transport processes. [Med-Science 2024; 13(4.000): 1030-8]